QUR’ANIC SCIENCE: RAPID GUIDE ON THE OCCASIONS OF THE QUR'ANIC REVELATION AND ITS BENEFIT - Yusuf Olawale Owa-Onire Uthman (al-Afkar, Journal For Islamic Studies, 2022)
The paper deals with the Islamic revelation as a concept, by stating the position of understanding its occasions through the core of the Qur’anic contest and the notion of the prophetic tradition, Hadith, and his companions, the possible benefits from the study is derived from studying this particular topic in the field of Quranic science and tafsir. The information about the method adopted in the study is given and available in the research text.